Non-aqueous template-assisted synthesis of mesoporous nanocrystalline silicon orthophosphate1. Issue 90 (1st October 2015) - Styskalik, Ales; Skoda, David; Moravec, Zdenek; Roupcova, Pavla; Barnes, Craig E.; Pinkas, Jiri
<x xml:space="preserve">Abstract</x> Mesoporous nanocrystalline silicon orthophosphate Si5P6O25 was synthesized by the non-hydrolytic sol–gel reaction in the presence of Pluronic P123 template and displays superior catalytic activity and selectivity in methylstyrene dimerization.